Public information needs after the poisoning of Alexander Litvinenko with polonium-210 in London: cross sectional telephone survey and qualitative analysis. Issue 7630 (1st November 2007) - Rubin, G James; Page, Lisa; Morgan, Oliver; Pinder, Richard J; Riley, Paul; Hatch, Stephani; Maguire, Helen; Catchpole, Mike; Simpson, John; Wessely, Simon
Abstract : Objectives To identify public perceptions of the risk to health after the poisoning of Alexander Litvinenko with polonium-210 ( 210 Po) in London and to assess the impact of public health communications. Design Cross sectional telephone survey and qualitative interviews. Setting London, United Kingdom. Participants 1000 people completed the cross sectional survey and 86 potentially exposed people completed the qualitative interviews. Main outcome measures Perception of risk to personal health after the 210 Po incident. Qualitative interviews were analysed with an emphasis on information needs. Results 11.7% of the survey sample (n=117) perceived their health to be at risk. Aside from personal variables the main predictors of perceived risk to health were believing that the incident was related to terrorism (odds ratio 2.7, 95% confidence interval 1.5 to 4.6) rather than to espionage, that it was targeted at the wider public rather than one person (5.9, 3.2 to 10.9), and that it could affect people who had not been in the contaminated area (3.2, 2.1 to 5.1). Participants in the qualitative interviews were generally satisfied with the information they had received, although they would have preferred more information about their individual risk of exposure, the results of their urine tests, and the health implications of the incident. Conclusions Perceptions of the public that the 210 Po incident in London in 2006 was related to espionage helped to reassure them that the risks to personal health were low. In the event of future incidents it is important to ensure that detailed, comprehensible information about the risks of any exposure is available.